Pronounced solvent effect on the composition of binary self-assembled monolayers with embedded dipole moments - Sauter, Eric; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
The formation and properties of binary thiolate self-assembled monolayers (SAMs), comprised of precursors featuring a short heteroaromatic backbone, consisting of a nonpolar phenyl ring and a polar pyrimidine group, embedded in two opposite orientations, were investigated in the context of work function engineering. The SAMs were prepared by coadsorption of both constituents dissolved in either tetrahydrofuran (THF) or ethanol, exhibiting a strong solvent effect. In the case of THF, the SAM composition nearly mimicked that of the primary solutions, with a slight preference of the 50%-50% relation, which was accompanied by the respective gradual variation of the work function, allowing its fine-tuning within the 4.0-4.9 eV range for Au(111). In the case of ethanol, a strongly preferential adsorption of one of the components was observed, limiting significantly the range of the work function variation. The effect of the solvent was tentatively explained by the different abilities of THF and ethanol to build hydrogen bonds to the SAM precursors, affecting their adsorption and self-assembly behavior. The composition and morphology of the binary SAMs were monitored by the electrostatic effects in photoemission, manifesting these effects as a useful experimental tool and a fingerprint parameter for the work function estimation.